2022
DOI: 10.3389/fvets.2022.840416
|View full text |Cite
|
Sign up to set email alerts
|

Rural Raccoons (Procyon lotor) Not Likely to Be a Major Driver of Antimicrobial Resistant Human Salmonella Cases in Southern Ontario, Canada: A One Health Epidemiological Assessment Using Whole-Genome Sequence Data

Abstract: Non-typhoidal Salmonella infections represent a substantial burden of illness in humans, and the increasing prevalence of antimicrobial resistance among these infections is a growing concern. Using a combination of Salmonella isolate short-read whole-genome sequence data from select human cases, raccoons, livestock and environmental sources, and an epidemiological framework, our objective was to determine if there was evidence for potential transmission of Salmonella and associated antimicrobial resistance det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Raccoons are more liable to be net recipients of AMR than drivers when compared to human populations. 58 Thus, humans appear to pose more of an AMR threat to these wildlife populations than vice versa. However, work on wildlife zoonoses in Spain demonstrates that wildlife-to-human AMR risks are non-negligible and likely higher for wildlife that readily traverses into and throughout the built environment.…”
Section: Risk To Humansmentioning
confidence: 99%
“…Raccoons are more liable to be net recipients of AMR than drivers when compared to human populations. 58 Thus, humans appear to pose more of an AMR threat to these wildlife populations than vice versa. However, work on wildlife zoonoses in Spain demonstrates that wildlife-to-human AMR risks are non-negligible and likely higher for wildlife that readily traverses into and throughout the built environment.…”
Section: Risk To Humansmentioning
confidence: 99%
“…Studies have shown a high occurrence of diverse Salmonella serovars belonging mostly to S. enterica [101]. Uncommon subspecies, S. enterica subspecies diarizonae 40:i: z 53, z54 and 48:k z57 have been reported in free-living adders and humans [101,102]. Salmonella shedding in snakes draws attention to possible zoonotic and epidemiological impacts, much more so in countries where snakes are handled, kept Available at www.onehealthjournal.org/Vol.9/No.1/1.pdf as pets and consumed by omnivorous animals, including man [101].…”
Section: Role Of Snakes In the Epidemiology Of Salmonellamentioning
confidence: 99%
“…Salmonella spp. are found in the gastrointestinal tracts of both domestic [ 6 ] and wild animals [ 7 ], as well as in humans [ 8 ]. They are transmitted through feces into agricultural produce [ 9 ], particularly leafy vegetables, during irrigation, cultivation, and processing [ 10 ], and they can spread from one animal to another (domestic to wild and vice versa) and from one person to another.…”
Section: Introductionmentioning
confidence: 99%